THE URGENCY OF ESTABLISHING THE MERAH PUTIH VILLAGE COOPERATIVE IN REALIZING VILLAGE ECONOMIC SELF-RELIANCE - Risman Setiawan (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2026)
This study analyzes the urgency of establishing the Merah Putih Village Cooperative to achieve village economic self-reliance through a normative legal approach. The primary issues addressed include the role of Presidential Instruction No. 9 of 2025 as a policy foundation for accelerating the formation of village cooperatives, and the integration of such policies within the legal frameworks of cooperative law, village law, people’s economic empowerment, and economic democracy principles. The research adopts legislative and conceptual methodologies, drawing on primary legal sources such as legislation and secondary sources including academic articles, legal journals, and scholarly studies. Findings demonstrate that the establishment of the Merah Putih Village Cooperative is normatively, economically, and institutionally urgent, as it can enhance access to capital, distribution of production outputs, marketing of local products, food security, and economic participation within the village community. Nevertheless, its effectiveness relies on regulatory clarity, cooperative governance, human resource capacity, synergy with Village-Owned Enterprises (BUM Desa), and ongoing oversight. The study concludes that the Merah Putih Village Cooperative could serve as a strategic instrument for village economic self-reliance if implemented in a participatory, transparent, and locally grounded manner.